2014
DOI: 10.3109/13880209.2014.924151
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, antioxidant, and TNF-α lowering properties of extract of the traditionally used plantIxeris gracilisin alloxan-induced diabetic mice

Abstract: The study supports the inclusion of Ixeris gracilis in the list of plants with antidiabetic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…DC.] contributes to the antioxidative and antidiabetic potential of plants extracts (Syiem and Warjri 2015). In this study, compared with vehicle-treated ZDF (fa/fa) rats, FJG treatment resulted in the recovery of the decreased levels of SOD and CAT activity accompanied with the inhibition of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…DC.] contributes to the antioxidative and antidiabetic potential of plants extracts (Syiem and Warjri 2015). In this study, compared with vehicle-treated ZDF (fa/fa) rats, FJG treatment resulted in the recovery of the decreased levels of SOD and CAT activity accompanied with the inhibition of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Stebbins (Asteraceae), traditionally used by local communities of Meghalaya in India, is listed as plant with antidiabetic potential. Administration of methanolic extract (250 mg/kg) for 12 days to alloxan-induced diabetic mice improved glucose tolerance, glycemic control, and activities of GPx and SOD in the liver, kidney, and brain [43]. Trigonella foenum graecum L. (fenugreek) is being used as folk medicine for diabetes treatment and several studies have demonstrated that fenugreek seed extract, mucilage of seeds and leaves have hypoglycemic effect in experimental diabetic animals and in humans [44,45].…”
Section: Plants In the Service Of Alleviation Of Diabetic Complicationsmentioning
confidence: 99%
“…A natural extract from Centella asiatica, rich in ascorbic acid, asiatic acid, oleanolic acid, stevioside, stigmasterol and α-humulene protects diabetes tissues from stress via antioxidant and anti-inflammatory mechanisms eliciting brain reduced levels of malondialdehyde, TNF-α, IFN-γ, IL-4 or IL10 [127]. Similar outcomes have been reported for Ixeris gracilis extract used in mice with alloxan-induced diabetes [128]. Specific assessment of mitochondrial status in STZ-induced diabetes has also revealed the capacity of Malvastrum tricuspidatum extract to restore oxidative damage [129] (Tables 1 and 2, and Figure 1).…”
Section: Natural Compounds and Central Complications In Dmmentioning
confidence: 81%